The Power of the Word in Sophocles’ Philoctetes - Anthony J. Podlecki (Greek, Roman, and Byzantine Studies, 2003)
<!--StartFragment--> The play's central theme is a failure in communication, λόγος, as Philoctetes, Odysseus, and Neoptolemus are unable to express themselves so as to come to terms with one another. <!--EndFragment-->